Purity and concentration dependence of piezoelectricity and thermal conductivity of boron nitride nanotubes - Kang, Shin Hye; Choi, Gyeong Min; Rahmannezhad, Javad; Kim, Chunghun; Kim, Young-Kyeong; Ahn, Seokhoon; Jang, Se Gyu; Kim, Myung Jong; Lee, Heon Sang (Materials Research Society, 2022)
A method to quantify the purity of boron nitride nanotubes (BNNTs) by defining purity index and determine their physical properties has been developed. The purity index, diameter, and length of the BNNTs were measured by analyzing SEM images after the dropwise addition of the dispersed BNNTs in solution onto a porous anodic aluminum oxide (AAO) membrane. The composite materials containing BNNTs were prepared by a hot press method to measure physical properties. The thermal conductivity and piezoelectricity of the BNNT composite materials were measured by varying the purity index or types of BNNT. The thermal conductivities were well-fitted to the Maxwell model, showing good dispersion, and the piezoelectric voltage was generally correlated with the purity index of the BNNTs. We believe, this study will promote the application of BNNTs by helping to provide proper methods for the purity and related physical property analyses.